2020
DOI: 10.1371/journal.pone.0235865
|View full text |Cite
|
Sign up to set email alerts
|

Outcome markers of ART-treated HIV+ patients with early stage Kaposi’s sarcoma

Abstract: HIV-associated/epidemic Kaposi's sarcoma (EpKS) is an AIDS-defining angio-proliferative malignancy. It can be treated with antiretroviral therapy (ART) alone or with ART plus cytotoxic chemotherapy. ART-treated EpKS can either respond or worsen upon treatment. This study aimed at identifying immunological markers of ART-treatment response. We compared responders (those with clinical EpKS tumor regression) versus poor responders (those with progressive or non-responsive EpKS). We measured plasma cytokine and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…IL-5 is a Th2 cytokine that promotes terminal differentiation of B cells into antibody-secreting plasma cells, and is also an important factor in the differentiation and maturation of eosinophils [ 14 , 15 ]. In a previous study, we observed that higher levels of plasma IL-5 were associated with a good treatment outcome for ART-treated HIV-associated KS [ 12 ]. However, in that study, IL-5 was not correlated with KSHV neutralizing antibodies (nAb).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-5 is a Th2 cytokine that promotes terminal differentiation of B cells into antibody-secreting plasma cells, and is also an important factor in the differentiation and maturation of eosinophils [ 14 , 15 ]. In a previous study, we observed that higher levels of plasma IL-5 were associated with a good treatment outcome for ART-treated HIV-associated KS [ 12 ]. However, in that study, IL-5 was not correlated with KSHV neutralizing antibodies (nAb).…”
Section: Discussionmentioning
confidence: 99%
“…In KS, IL-6 has been found to be elevated in both HIV-associated and non-HIV-associated KS [ 20 ]. In addition, IL-6 was observed to be higher among individuals with early-stage HIV-associated KS who had disease progression compared those who responded favorably to antiretroviral therapy [ 12 ]. Our findings, in comparison to previous studies highlight the pleotropic effects of IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KSHV has also been observed to encode the chemokine ligands (vCCL1, vCCL2, and vCCL3) that bind to chemokine receptors (CCR8, CCR3, and CCR4) expressed on the surface of Th2 cells and hence result in chemoattraction of Th2 lymphocytes to infection sites [ 62 ]. This may explain the observed rise in anti-KSHV antibodies in KS patients [ 63 ]. However, there appears to be no role of these neutralizing antibodies (nAb) in controlling KSHV infection or KS [ 63 ].…”
Section: Adaptive Responses In Kshv Infection and Ksmentioning
confidence: 99%
“…This may explain the observed rise in anti-KSHV antibodies in KS patients [ 63 ]. However, there appears to be no role of these neutralizing antibodies (nAb) in controlling KSHV infection or KS [ 63 ]. The high KSHV nAb in KS patients may be attributed to persistent production of antibody-associated cytokines (IL-4 and IL-5) and not necessarily the control of KSHV infection or KS [ 63 , 64 ].…”
Section: Adaptive Responses In Kshv Infection and Ksmentioning
confidence: 99%